Superior outcome of corneal collagen cross‐linking using riboflavin with methylcellulose than riboflavin with dextran as the main supplement. Issue 4 (3rd October 2018) - Thorsrud, Andreas; Hagem, Anne Marie; Sandvik, Gunhild Falleth; Drolsum, Liv
Abstract: Purpose: To compare the effect of corneal collagen cross‐linking (CXL) on progressive keratoconus using 0.1% riboflavin with either dextran or methylcellulose as the main supplement. Methods: In a comparative case series, CXL was performed in 40 patients (40 eyes) using a riboflavin solution containing either dextran (dextran–riboflavin; n  = 20) or methylcellulose (methylcellulose–riboflavin; n  = 20). Changes in central corneal thickness (CCT), Scheimpflug tomography, maximal keratometry reading ( K max ), visual acuity (VA) and endothelial cell density (ECD) were recorded. Stromal changes one month after surgery were analysed using optical coherence tomography (OCT) and in vivo confocal microscopy (IVCM). Results: The CCT was significantly higher in the methylcellulose–riboflavin group during the CXL procedure. The IVCM demarcation line depth was 274 ± 80 (SD) μ m in the dextran–riboflavin group and 442 ± 80  μ m in the methylcellulose–riboflavin group (p < 0.001). Complete absence of keratocytes in the pre‐endothelial stroma was found in none of the corneas treated with dextran–riboflavin and in 42% of the corneas treated with methylcellulose–riboflavin. Visibility of the OCT demarcation line was significantly lower in the methylcellulose–riboflavin group. K max and corrected distance visual acuity were improved in the methylcellulose–riboflavin group and stable in the dextran–riboflavin group after 2 years. Endothelial cell density (ECD) was stable in both groups. Conclusion: We found deeper structural changes in the methylcellulose–riboflavin group than in the dextran–riboflavin group. This may be explained by different riboflavin solution properties and raises safety concerns. The study also indicates improved effect using methylcellulose–riboflavin than dextran–riboflavin, possibly explained by deeper stromal CXL effect.